Prevalence and risk factors of retinal vein occlusion: the Gutenberg Health Study - Ponto, Katharina; Mirshahi, Alireza (Journal of thrombosis and haemostasis, 2015)
Objective: To determine the age- and sex-specific prevalence and determinants of retinal vein occlusions (RVOs) in a large population-based German cohort. Methods: The investigation included 15 010 participants (aged 35-74 years) from the Gutenberg Health Study. We determined the prevalence of RVO (central retinal vein occlusion [CRVO] and branch retinal vein occlusion [BRVO]) for the local population by assessing fundus photographs of 12 954 (86.3%; 49.8% women and 50.2% men) participants. Further, we analyzed the associations of RVO with cardiovascular, anthropometric, and ophthalmic parameters. Results: The weighted prevalences of RVO, CRVO, and BRVO were 0.40%, 0.08%, and 0.32%, respectively. Men were 1.7 times more frequently affected by RVO than were women. Prevalence of RVO was 0.2% in participants aged 35-44 and 45-54 years, respectively, 0.48% in those aged 55-64 years, and 0.92% in those aged 65-74 years. Of persons with RVO, 91.5% had one or more cardiovascular risk factor or disease vs. 75.9% of persons without RVO. BRVO was associated with arterial hypertension (odds ratio 2.69, 95% confidence interval 1.27-5.70) and atrial fibrillation (3.37, 1.24-9.12) and CRVO with higher age (7.02, 1.63-30.19) and a family history of stroke (4.64, 1.18-18.25). Median visual acuity (base 10 logarithm of minimum angle of resolution) was 0.2 in persons with RVO vs. 0.05 in those without. Conclusion: The prevalence of RVO in this German population was 0.4%, and men were 1.7 times more frequently affected than women. CRVO was associated with higher age and a family history of stroke, and BRVO was associated with arterial hypertension and atrial fibrillation.
Gesehen am 17.12.2018